2013
DOI: 10.1371/journal.pone.0072237
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental, Biotic and Spatial Factors on Diatom Metacommunity Structure in Swedish Headwater Streams

Abstract: Stream assemblages are structured by a combination of local (environmental filtering and biotic interactions) and regional factors (e.g., dispersal related processes). The relative importance of environmental and spatial (i.e., regional) factors structuring stream assemblages has been frequently assessed in previous large-scale studies, but biotic predictors (potentially reflecting local biotic interactions) have rarely been included. Diatoms may be useful for studying the effect of trophic interactions on com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 63 publications
5
58
1
Order By: Relevance
“…4). This was in accordance with Abbreviations of environmental variables as in Table 2 Hydrobiologia (2014) 732:49-60 55 Passy (2007) and Tang et al (2013), but not consistent with Potapova & Charles (2002), Urrea & Sabater (2009), Smucker & Vis (2011 and Göthe et al (2013). For example, Passy (2007) found that the unique contribution of spatial dataset (16%) to the explained diatom variance was higher than that of environmental variables (9%).…”
Section: Diatom-environmental Relationships Across a Large Spatial Scalementioning
confidence: 49%
See 2 more Smart Citations
“…4). This was in accordance with Abbreviations of environmental variables as in Table 2 Hydrobiologia (2014) 732:49-60 55 Passy (2007) and Tang et al (2013), but not consistent with Potapova & Charles (2002), Urrea & Sabater (2009), Smucker & Vis (2011 and Göthe et al (2013). For example, Passy (2007) found that the unique contribution of spatial dataset (16%) to the explained diatom variance was higher than that of environmental variables (9%).…”
Section: Diatom-environmental Relationships Across a Large Spatial Scalementioning
confidence: 49%
“…However, Urrea & Sabater (2009) got a less influence of spatial factors (6.1%) than physicalchemistry variables (11.3%) on diatom community. Similarly, local environmental variables were considered to have much higher contribution (than spatial variables) to the total explained variation of diatom data (Potapova & Charles, 2002;Smucker & Vis, 2011;Göthe et al, 2013). The large sampling scale in the present study is likely a reason for the above finding.…”
Section: Diatom-environmental Relationships Across a Large Spatial Scalementioning
confidence: 62%
See 1 more Smart Citation
“…We suggest that in a medium-order stream that it is mainly velocity that is shaping the diatom community at the decimeter scale, as shown by PASSY (2001). At smaller scales, grazing could have an important impact on algal communities (GOTHE et al 2013, O'DRISCOLL et al 2014, probably together with historical events following dispersal (MÜLLER-HAECKEL 1976) and also the named »complex interaction of abiotic conditions« (e.g. KEMP and DODDS 2001).…”
Section: Factors Impacting At Spatial Scalementioning
confidence: 78%
“…Unfortunately, our landscape data were limited to a subset of variables, lacking information on habitat structure or occurrences of other species than cichlids. It is likely that cichlid species composition is structured not only by underlying landscape gradients but also by biotic interactions (Rae et al, 2006;Meier et al, 2010;Göthe et al, 2013). Whether this is competition, food resources, or some other aspect of interspecific interactions remains to be seen in future studies.…”
Section: Community Turnover Exceeds Predictions By Space and Environmentmentioning
confidence: 96%